Firm-Level Technology Adoption in Vietnam - Cirera, Xavier (The World Bank, 2021)
This paper describes the results of a new firm survey to measure technology use and adoption implemented prior to the COVID-19 pandemic in Vietnam. It analyzes the use and adoption of technology among Vietnamese firms and identifies some of the key barriers to adoption and diffusion. The analysis offers new and important stylized facts on firm-level use of technologies. First, although access to the internet is almost universal in Vietnam, firms had low digital readiness to face the COVID-19 pandemic; and the share of establishments with their own website, social media, and cloud computing is still small. Second, the use of Industry 4.0 technologies is incipient. Third, the technology gap with the use of frontier technologies in some general business functions, such as quality control, production planning, sales, and sourcing and procurement, is large. Fourth, the manufacturing sector faces the largest technological gap, larger than services and agricultural firms. The analysis of the main barriers and drivers to technology adoption and use shows the importance of good management quality for technology adoption, and that there is a technology premium associated with exporting activities. Finally, the analysis also shows that firms are largely unaware of the available public policy support for technology upgrading